Technical performance scores associate with early prognosis of tetralogy of Fallot repair - Ailixiati Alifu; Haifan Wang; Renwei Chen (Frontiers Media S.A., 2024)
ObjectiveThis study aimed to investigate the relationship between technical performance scores (TPS) and the early prognosis of tetralogy of Fallot repair (TOF).MethodsA retrospective study was conducted on TOF repair patients at our center from Oct 2017 to Oct 2022. Patients were classified into Class 1 (no residua), Class 2 (minor residua), or Class 3 (major residua) based on TPS derived from predischarge echocardiograms and need for reintervention. Statistical methods were used to assess the association between TPS and early prognosis.ResultsA total of 75 TOF repair patients (40% female, 60% male) were analyzed and categorized into TPS1 (24%), TPS2 (53.3%), and TPS3 (22.6%) based on pre-discharge echocardiographic findings. The median follow-up time was 7.0 months. The multivariable Cox regression analysis indicated that TPS3 scores are associated with a 12.68-fold increase in risk compared to TPS1 and TPS2 scores [95% CI = 12.68 (0.9∼179.28), P = 0.06]. The Spearman rank correlation analysis revealed a weak positive correlation between TPS classification and low cardiac output syndrome (r = 0.26, P = 0.03). However, there were no significant differences in ICU stay or duration of mechanical ventilation among the groups.ConclusionTPS3 after intracardiac TOF repair is associated with higher risk of early re-intervention, highlighting the importance of close follow-up and monitoring in this patient population. Patients who develop low cardiac output syndrome in the early postoperative period may have residual defects that require prompt identification.